PENGGUNAAN VIDEO TUTORIAL DALAM UPAYA MENINGKATKAN PRESTASI BELAJAR TIK PADA SISWA KELAS XII.IPS-1 - Sumantri, Ucu (Universitas Siliwangi, 2019)
The problem of ICT learning in SMAN 1 Bantarujeg, Majalengka Regency is the low student achievement because the teacher still uses the conventional method, the lecture method. This research is a class action research. The research took place in 2 cycles consisting of 4 meetings. This study consists of 4 stages, namely planning, implementation, observation, and reflection. Data collection uses observation sheets and tests. The results showed that the use of video tutorial media in ICT learning in class XII students. IPS-1 in SMAN 1 Bantarujeg, Majalengka Regency can improve student learning achievement. This increase can be seen from the end of the cycle test results. In cycle 1 the value of students who achieved completeness was 18 students or around 75%, then in cycle 2 it reached 22 students or around 91.66%. Thus, student achievement has exceeded the criteria for the success of actions that have been set at 70%